Country-Level Effectiveness and Accountability Review : Madagascar - Moyart, Manuel; Duflos, Eric; Latortue, Alexia; Lecuyer, Francois; Isern, Jennifer; Rauch, Hubert (CGAP and the World Bank, Washington, DC, 2014)
This Country-Level Effectiveness and Accountability Review (CLEAR) examines the efficacy of microfinance aid in Madagascar, based on an objective analysis of donor assistance for the sustainable development of financial systems targeting the poor. The three levels of the financial system are the micro level (e.g., retail institutions), the meso level (e.g., apex, technical service providers), and the macro level (e.g., regulations and policies). At the micro level, there is a large number of stakeholders, and an increasing interest of banks and private investors, including a predominant stake by the Decentralized Financial Systems (DFS), as well as major roles by the local Savings Institution and the Post Office. At the meso level, there is a supply of services such as auditing. Finally, at the macro level, coordination and supervision exist, and a specific legal framework on microfinance is in place. Notwithstanding, microfinance in Madagascar remains weak, and, concerns suggest DFSs carry structural weaknesses at various levels. Additionally, it is specified services in support of microfinance are still rare, and its quality it debatable. Professional organizations need to be strengthened, particularly as lack of reliable information on financial results is concerned. At the macro level, supervisory and coordinating agencies rely on limited means, whereas the legal framework is not fully supportive. Risks suggest potential market disruptions resulting from subsidies and interest rate hikes, an implication by which the Ministry of Agriculture not always agrees with the Microfinance National Strategy. Finally, the judicial system does not rely enough in favor of the development of the financial sector.